Implementing Discovery Learning Method in Teaching Reading Comprehension at Senior High School - Titi Damayanti; Sultan Baa; Fatimah Hidayahni Amin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This research aims at finding out: (1) whether EFL students’ reading comprehension improves with the Discovery Learning Method (DLM) in teaching reading or not, and (2) the students’ perceptions of the developing Reading Comprehension with the DLM. This research applied a pre-experimental with One Group Pre-test and Post-test design to assess the improvement of students’ Reading Comprehension and a questionnaire was used to find out the students’ perception of the DLM in English Reading Classroom. Thirty-six (36) students of XI Science 2 at SMAN 2 Baubau were selected as participants of the study using Cluster Random Sampling technique. The pre-test and post-test results were obtained from students’ reading tests and then analyzed by using IBM Statistic SPSS 25 Software. Questionnaire responses were classified into four (4) main indicators: the benefit, the interest, the activities, and the implementation. The study discovered: (1) the average result of the pre-test was 64.44 and in post-test was 76.91. It can be concluded that there is a significant effect of implementing DLM on students' Reading Comprehension; (2) the findings of students' perceptions based on the frequency, showed that average students agreed that DLM could improve their reading comprehension based on the four indicators: the benefit (63.9%), the interest (58.3%), the activities (50%), and the implementation (52.9%).